2016
DOI: 10.1136/bmjspcare-2015-000850
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of informal caregiver and named nurse assessment of symptoms in elderly patients dying in hospital using the palliative outcome scale

Abstract: ICGs are more reliable proxies than HCPs. A trend for overestimation of symptoms was found in both groups which may lead to undervaluation of the quality of life by proxy and overtreatment of symptoms. This highlights the need to always use the patient report when possible, and to be aware of the potential flaws in proxy assessment. Reasons for overestimation by proxies deserve further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 35 publications
(49 reference statements)
4
19
0
Order By: Relevance
“…Additionally, studies using the POS to evaluate needs and symptoms of terminal elderly show that care professionals tend to overestimate some symptoms, especially in psychological domains, such as finding life worth living and sharing feelings. This could also explain the higher dementia scores in the population of older adults with dementia symptoms . Care professionals also suggested a low self‐worth, especially in people with dementia.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Additionally, studies using the POS to evaluate needs and symptoms of terminal elderly show that care professionals tend to overestimate some symptoms, especially in psychological domains, such as finding life worth living and sharing feelings. This could also explain the higher dementia scores in the population of older adults with dementia symptoms . Care professionals also suggested a low self‐worth, especially in people with dementia.…”
Section: Discussionmentioning
confidence: 97%
“…This could also explain the higher dementia scores in the population of older adults with dementia symptoms. 28 Care professionals also suggested a low self-worth, especially in people with dementia. The study of Brandt et al of residents in the last days of their lives showed unfavorable scores on selfworth for both people with dementia and without dementia in the final days.…”
Section: Discussionmentioning
confidence: 99%
“…This underestimation of both physical and psychological symptoms is congruent with most previous studies, although Dawber et al found an overestimation of physical and psychological symptoms in an acute hospital population. 30 Although it is known that psychological symptoms are difficult to interpret and are more likely to be overlooked and undertreated in daily care, 24 our results indicate that both physical and psychological symptom are at risk for underestimation and thus undertreatment in the absence of self-report.…”
Section: Concordancementioning
confidence: 69%
“…Symptom intensity is measured on a five-point verbal rating scale (0 ¼ no symptom to 4 ¼ overwhelming), in concordance with the Palliative care Outcome Scale. 30 Well-being is measured on a 0e10 scale (0 ¼ best possible e10 ¼ worst possible) in concordance with the USD.…”
Section: Nurses' Assessment Of Symptom Intensity and Wellbeingmentioning
confidence: 99%
“…Both studies found higher agreement between patients and ICG than between patients and HCP. 11,12 Jones et al analyzed quality-of-life ratings from terminally ill patients with cancer having ICGs' and HCPs' ratings, and both ratings were statistically and clinically significantly different from patientreported experiences. 13 The American questionnaire QoDD 14 is 1 of 6 currently available instruments assessing this important issue of certainty 15 in clinical care and research projects.…”
Section: Introductionmentioning
confidence: 99%